A single-team case study of corrective exercises for upper-extremity injuries and movement dysfunction in collegiate swimmers - Quigley, K. G.; Fenner, M.; Pavilionis, P.; Murray, N. G. (Sports, 2025)
Swimming research has determined that rounded shoulders, forward head, and scapular dyskinesis are common imbalances that may lead to injury without correction. This case study aimed to evaluate a preventative exercise program designed to reduce injuries, correct postural deviations, and improve shoulder function over one collegiate swimming season. Twenty female NCAA Division I swimmers (average age = 21.6 ± 1.3 years) participated over 25 weeks, completing pre-, mid-, and post-season assessments of injury rates, shoulder range of motion, and stability using standardized tests. Injuries were included as diagnosed and reported by an athletic trainer. Testing included internal rotation, external rotation, the Hawkins-Kennedy test, Neer`s sign, Sulcus sign, and the Closed Kinetic Chain Upper-Extremity Stability Test (CKCUEST). Compared to the season prior with no intervention, swimmers who completed the program were 44% less likely to sustain an upper-extremity injury, as assessed from the CKCUEST scores (p < 0.01 for all metrics), shoulder internal rotation (p < 0.01 for both shoulders), and total range of motion (p < 0.01 for both shoulders). These findings suggest that a targeted corrective exercise program can effectively reduce injury rates and improve shoulder mobility and function in collegiate athletes. The interpretation of these results is limited by the study`s non-randomized design and absence of a control group.